2002
DOI: 10.1159/000065303
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Peroxisome Proliferator-Activated Receptor-g Inhibits Apoptosis Induced by Serum Deprivation in LLC-PK1 Cells

Abstract: Peroxisome proliferator-activated receptor-γ (PPARγ) belongs to a superfamily of nuclear receptors, which plays important roles in lipid and glucose metabolism. However, expression of PPARγ in extra-adipose tissues and stimulation of apoptosis by PPARγ activators has been previously reported. We investigated the functions of PPARγ using a clonal kidney cell line (LLC-PK1). RT-PCR revealed the expression of PPARγ in LLC-PK1 cells. The cells accumulated fat droplets and increased β-oxidation of free fatty acids … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2003
2003
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 37 publications
0
6
0
1
Order By: Relevance
“…RGTZ protects renal, myocardial and cerebral ischemia 34,45,51,52 and its antiapoptotic effect is regarded as a protective mechanism. In an in vitro study, troglitazone suppressed apoptosis of clonal tubular epithelial cells 53 . In our preliminary study, we found that RGTZ prevented CsA‐induced apoptotic death of renal tubular cell, which is a main cause of cell death in CsA‐induced renal tubular injury 54–56 .…”
Section: Mechanisms Of Renoprotection By Pparγ Agonistsmentioning
confidence: 79%
“…RGTZ protects renal, myocardial and cerebral ischemia 34,45,51,52 and its antiapoptotic effect is regarded as a protective mechanism. In an in vitro study, troglitazone suppressed apoptosis of clonal tubular epithelial cells 53 . In our preliminary study, we found that RGTZ prevented CsA‐induced apoptotic death of renal tubular cell, which is a main cause of cell death in CsA‐induced renal tubular injury 54–56 .…”
Section: Mechanisms Of Renoprotection By Pparγ Agonistsmentioning
confidence: 79%
“…In addition to our report, several groups have found that PPAR␥ improves cell survival in other systems. Haraguchi et al 37 reported that several PPAR␥ agonists inhibit serum starvation induced apoptosis in kidney cells. In addition, it has been shown that infusion of 15d-PGJ 2 and rosiglitazone resulted in reduction in size of brain infarct 38 as well as myocardial infarct in rats.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, ciglitazone reduced MK886-induced cell apoptosis Figure 6). Interestingly, two recent reports [34,35] have shown that several thiazolidinedione PPARγ agonists can protect lymphocytes and LLC-PK1 cells from apoptosis.…”
Section: Modulation Of Mk886-induced Apoptosis By Wy14643 and Ciglitamentioning
confidence: 99%